Assessment of Anxiety in Patients With Epilepsy: A Literature Review - Rauh, Raphael; Schulze-Bonhage, Andreas; Metternich, Birgitta (Frontiers in Neurology, 2022)
Objective: Approximately 20% of people with epilepsy (PWE) suffer from anxiety. These fears are quite diverse and may manifest periictally or interictally, be part of seizure’s semiology, or an expression of reactive psychological distress from seizures themselves. Our review addresses the question what screening tools are used in clinical care and epileptological research to capture the complexity of epilepsy-specific anxieties. Method On 2021/11/11, we entered a search string in PubMed that covered our research interest as completely as possible. We also screened the bibliographies of our findings and followed PubMed's recommendations. From the assessments we found in the included studies, we extracted domains that represent the range of manifestations of anxiety, in order to compare the tools and to discuss to what extent they are suitable for assessing epilepsy-specific anxieties. Results We screened 1621 abstracts. In total, we identified 24 different anxiety assessments. In addition to the psychiatric assessments in use, we found 6 tools that were designed to assess epilepsy-specific anxieties. The latter focus on different aspects of epilepsy-specific anxieties. In some cases, the conceptual frameworks are not sufficiently transparent or divergent. Conclusion Because a diagnosis of epilepsy can result in or seizures may appear as anxiety, it is important to better understand this psychological burden and address it therapeutically, if necessary. There is a need for screening tools that integrate specific points of a variety of assessments, so as to cover the broad range of epilepsy-specific fears. None of the assessments we found meets this integrative perspective. At the same time, the appropriate design of such a required tool presupposes a conceptual framework of what should be considered as epilepsy-specific anxiety.